Effects of Interactive Video Game-Based Exercise on Balance in Diabetic Patients with Peripheral Neuropathy: An Open-Level, Crossover Pilot Study. (6th March 2019) - Hung, Erica Shih-Wei; Chen, Shih-Ching; Chang, Fan-Chien; Shiao, Yaojung; Peng, Chih-Wei; Lai, Chien-Hung
Abstract : Purpose. This study evaluated the effects of interactive video game-based (IVGB) exercise on balance in diabetic patients with peripheral neuropathy. Materials and Methods. Twenty-four patients were randomly assigned to two groups (12 participants per group). Group A received IVGB training for the first 6 weeks, with no exercise in the subsequent 6 weeks. Group B had no exercise for the first 6 weeks and then underwent IVGB training in the subsequent 6 weeks. For all participants, the Modified Falls Efficacy Scale (MFES), Time Up and Go (TUG) test, Berg Balance Scale (BBS), and Unipedal Stance Test (UST) were employed at weeks 0, 6, and 12 of the experiment. Results. BBS, right-leg UST, and TUG test scores significantly improved after IVGB intervention, whereas MFES and left-leg UST tended to improve after IVGB intervention. Conclusions. This study revealed that 6-week balance-based exercise training using the IVGB system exerted positive effects on functional balance in patients with diabetic peripheral neuropathy (DPN).